Inflammatory biomarkers in the prediction of residual cardiovascular risk in patients with metabolic syndrome: An integrative literature review (Research, Society and Development, 2025)
Metabolic syndrome represents a set of interrelated metabolic alterations that significantly increase the risk of cardiovascular events. Even with control of traditional risk factors, many patients continue to experience adverse outcomes, characterizing what is known as residual cardiovascular risk. Recent studies have shown that chronic low-grade inflammation plays a fundamental role in this process, particularly biomarkers such as interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), and high-sensitivity C-reactive protein (hs-CRP). The objective of this article is to conduct an integrative literature review on the clinical applicability of the inflammatory biomarkers IL-6, TNF-α, and hs-CRP in the stratification of residual cardiovascular risk in patients with metabolic syndrome, highlighting the main findings, challenges, and future perspectives in the management of this population. Available evidence on the association between serum levels of these markers and the occurrence of cardiovascular events was analyzed, as well as their potential use in risk stratification beyond traditional parameters. The results suggest that these biomarkers have promising prognostic value and may contribute to a more personalized and effective approach in the secondary prevention of cardiovascular events. Despite advances in understanding this relationship, further research is still needed to consolidate their routine use in clinical practice and establish inflammation-based therapeutic protocols.